Teatro playback na escola : "um estudo para uma proposta pedagógica" - Barbosa, Renato Barros (2020)
The proposed article aims to present Playback Theater, its origin and its application as a pedagogical proposal, aimed at students in the eighth grade of Elementary School II. This proposal will seek, through the use of this methodology, to favor the development of creative artistic skills, since it is a theatrical modality whose improvisation is its main characteristic, while at the same time allowing the student to experience their stories immediately transformed into art. Considering that theatrical language is part of the school curriculum, promoting self-knowledge, the development of expression, communication, facilitating the process of interaction between students and mutual respect, thus contributing to the student's integral education. As a methodology, to obtain the objectives suggested in the work, we used the techniques of theatrical games, as well as the forms used by Playback Theater (fluid sculptures, pairs, choir, comic book, three moments, confabulating, etc.). In this way, students / actors can achieve the objectives suggested by the work.